2011
DOI: 10.1080/15389588.2011.607479
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating Attentional Demand in a Simulated Driving Assessment: The Roles of Age and Driving Complexity

Abstract: The findings are highly consistent with the literature on road complexity and attention that show that increased driving complexity is associated with poorer performance on tasks designed to concurrently assess attention, an effect that is more pronounced for older drivers. The results point to intrinsic and extrinsic factors that contribute to motor vehicle collisions (MVCs) among older drivers. The relevance of these findings is discussed in relation to interventions and future research aimed at improving ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…This is because there is a high number of school children generated from nearby secondary school, people coming back from work, and those going for shopping at the nearby shopping complex (mostly between age groups of 25-35 and 35-45 years old. This findings is in consistent to past findings [14]) which reported that when the complexity of a road is high especially during heavy traffic, the performance of drivers are low regardless of age groups which may contribute to greater chances of crash occurrence.…”
Section: Composite Road Environment Risk Index Vs Crash Datasupporting
confidence: 82%
“…This is because there is a high number of school children generated from nearby secondary school, people coming back from work, and those going for shopping at the nearby shopping complex (mostly between age groups of 25-35 and 35-45 years old. This findings is in consistent to past findings [14]) which reported that when the complexity of a road is high especially during heavy traffic, the performance of drivers are low regardless of age groups which may contribute to greater chances of crash occurrence.…”
Section: Composite Road Environment Risk Index Vs Crash Datasupporting
confidence: 82%
“…The scenario was based on a simulated driving evaluation course developed by Weaver et al (2009) (see also Lemieux et al, 2014;Stinchcombe et al, 2011). Modifications were made to the original course in order to divide it into six road sections, each allowing the inclusion of any of the six challenging events described below and the counterbalancing of the sequence of events across scenarios.…”
Section: Simulated Scenariomentioning
confidence: 99%
“…When resource demands exceed resource availability, performance can be impaired [ 27 ]. Mental workload increases with driving complexity [ 29 , 30 ]. Therefore, when considering the context of a driving study, scenarios need to be designed with an appropriate level of difficulty and mental workload to identify subtle differences in driving behavior.…”
Section: Introductionmentioning
confidence: 99%